Systematic review of IPSAS standards: The introduction of IPSAS in public establishments - Yassine, HILMI; Zahra, HAJRIOUI; KEZAZY Hamza, EL (Edelweiss Applied Science and Technology, 2024)
The ultimate objective of this paper is to examine the impact of the adoption of IPSAS in Morocco on the production of accounting and financial information, in order to inform decision-making processes. IPSAS ushered in a global revolution in public accounting reforms, and Morocco is among the nations that have adopted these standards, starting their implementation several years ago. The integration of IPSAS mobilises a theoretical and conceptual framework encompassing the theories and New Public Management (NPM), as well as the theory of public value. The aim is to harmonise accounting practices with global standards, thereby enhancing the transparency, comparability and credibility of financial information. However, the implementation of IPSAS in Moroccan institutions raises a number of issues and challenges, particularly in terms of adapting systems, training staff and managing costs. To deepen our understanding of this topic, we conducted a bibliometric analysis using the VOSviewer tool. This analysis enabled us to identify influential authors, collaborative networks, and the main and emerging themes in IPSAS research. The results show that the implementation of IPSAS helps to ensure good quality and transparency in public sector financial reporting, providing better information for financial management, accountability and decision making. IPSAS, as international accounting standards specific to the public sector, aim to improve the quality of financial reporting by public entities, thereby enabling more reliable resource allocation decisions and contributing to improved financial transparency and accountability.